TERRA INCOGNITA - LOTYŠSKO - EXPANZE ZNAČKY ZETOR NA MÍSTNÍM TRAKTOROVÉM TRHU - Pipal, David (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Tato diplomová práce analyzuje různé modely zastoupení při průniku na lotyšský traktorový trh společností Zetor a předkládá veškeré nezbytné informace k této problematice potřebné. Závěrem jsou navržené metody zastoupení vyhodnoceny a výstupem je předložení optimální varianty postupu. Tato varianta se stane předmětem strategického rozhodování managementu společnosti Zetor, který určí definitivní postup ve věci zastoupení na lotyšském trhu.

This Thesis analyses various representation models in the matter of Latvian tractor market penetration by Zetor brand products and herewith presents all necessary information concerning this problem. All suggested representation models are going to be evaluated and the output of this evaluation is the optimal model presentation for Zetor Group management. This authority is responsible for strategic decision of final representation model for Zetor brand products on Latvian tractor market.
TERRA INCOGNITA - LATVIA - THE ZETOR BRAND EXPANSION ON THE LOCAL TRACTOR MARKET
Keywords: Pobaltí; Lotyšsko; zahraniční obchod; export; zastoupení; fuzzy logika; Baltic Region; International Trade; Export; Business Representation Models; Fuzzy Logic